Political Economy’s Influence on ASEAN’s Competition Law: A Study on Selected ASEAN Members: Pengaruh Ekonomi Politik terhadap Hukum Persaingan ASEAN: Studi pada Beberapa Anggota ASEAN Tertentu - Ramaiah, Angayar Kanni; Hussein, Safinaz Mohd.; Porananond, Ploykaew; Dung, Tran Viet; Sirait, Ningrum Natasya; Amin, Wan Liza (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2025)
Competition law aims to promote fair market practices and prevent monopolistic behaviour, while political economy explores the relationship between economic systems and political institutions. Together, these disciplines shape the regulatory frameworks that oversee national markets and economic policies, encouraging competition and tackling issues such as inequality and market inefficiencies. In developing countries, the influence of political economy tends to be more significant than in developed nations, which usually benefit from more stable democratic institutions and stronger legal systems. Among ASEAN member states (AMS), there is notable variation in levels of economic development, policies, political structures, and legal frameworks. Consequently, each AMS’s unique political and legal history has influenced its approach to economic management and competition law, leading to distinct priorities and concerns. These political economy factors similarly impact the process of regional competition law integration among ASEAN countries. This paper explores how political economy shaped the enactment and enforcement of competition law in selected AMS: Malaysia, Vietnam, Thailand, and Indonesia. It analyses the underlying reasons for their specific reservations, exemptions, and priorities within their competition law. Using qualitative legal research and comparative analysis, the study reviews relevant political economy structures, statutes, regulations, and policies in the chosen AMS to assess their significance and influence on competition law administration. The findings indicate that ASEAN’s regional competition law alignment and integration must recognise each AMS’s broader internal political economy, which is vital for developing competitive markets within ASEAN.